2018
DOI: 10.30560/hssr.v1n2p43
|View full text |Cite
|
Sign up to set email alerts
|

Planning Educational Activities for Learning “Road Safety”

Abstract: In this paper, a project of the local sustainability network of schools in the area of Western Attica (Greece) is described. The subject of this project is “Road Safety”, and it was addressed to third grade pupils of junior high-schools. It has been planned as the result of collaboration between the local Secondary Education Directorate, a few voluntary organizations, some private Vehicle Technical Inspection Centers and the local traffic-police department. This educational activity had been mainly implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Bloom's taxonomy:  In the tasks aimed at remembering (No. 1,5,8,11,12,14,16) we tested pupils´ ability to repeat the knowledge, name, mark, fill in missing information, choose correct answer, e.g. : name road signs, mark colours at traffic lights with meaning, etc.…”
Section: Figure 1 Bloom´s Taxonomy Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Bloom's taxonomy:  In the tasks aimed at remembering (No. 1,5,8,11,12,14,16) we tested pupils´ ability to repeat the knowledge, name, mark, fill in missing information, choose correct answer, e.g. : name road signs, mark colours at traffic lights with meaning, etc.…”
Section: Figure 1 Bloom´s Taxonomy Modelmentioning
confidence: 99%
“…Road safety has been the subject of educational authorities [1] and of persistent international focus due to the widespread economic and social consequences of road accidents, especially fatalities, among young people [2]. Statistical analyses of road accidents have shown that children aged 5 to 14 are the most vulnerable group.…”
Section: Introductionmentioning
confidence: 99%